The Evaluation of Cognitive Load Significance for Mobile Learning Application via User Interface Design Violations - Faudzi M.A.; Ghazali M.; Cob Z.C.; Omar R.; Sharudin S.A. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer aided instruction; COVID-19; E-learning; Learning systems; NASA; Usability engineering; Classroom settings; Cognitive loads; Education systems; Face-to-face modes; Learning methods; Mobile Learning; NASA-TLX; Nielsen; Nielsen heuristic; User interface designs; User interfaces